Molecular docking and dynamics simulation study of telomerase inhibitors as potential anti-cancer agents. (2021) - Sherin, D.R.; Manojkumar, T.K.; Prakash, R.C.; Sobha, V.N.
Graphical abstract: Abstract: Normal cells' genomic identity is protected by telomeres and sometimes chromosomal instability was observed due to shortening of telomerase because of successive cell divisions. Reports indicate that telomerase length is crucial in determining telomerase activity which in turn leads to cancer initiation. It is reported that telomere length regulation has been identified as a plausible strategy for cancer diagnostics and treatment. In the present MS, we explored the telomerase inhibitory activity of catechin analogues and it's oligomers using computational methods. The structural properties of different ligands discussed in the MS were computed using density functional theory. Conformational effect of different chromene subunit such as 2R, 3R conformations were explored using computational methods. The stereochemical contributions to receptor binding such as intra ligand π-interactions of these ligands were also investigated. We herein propose that these stereochemical aspects of catechins and their oligomers as the most vital factor deciding the effective binding with the N-terminal domain of telomerase which is an efficient strategy in cancer therapy.